PERAN INTERNATIONAL LABOUR ORGANIZATION DALAM MELINDUNGI HAK ASASI PEKERJA MIGRAN INDONESIA DI MALAYSIA PADA TAHUN 2016 - 2019 - Haniifah Febriliyani, (2021)
The International Labor Organization (ILO) is an international organization that concentrates on promoting and protecting migrant workers' human rights. Indonesia is one of the ILO member countries that have problems with its migrant workers in Malaysia. Indonesian migrant workers (PMI) in Malaysia are vulnerable to various problems of the protection with PMI's human rights because Malaysia is known as a country that is less friendly to migrant workers. As a result, the number of PMI complaints about cases of human rights violations increased in 2016 - 2019. The number of PMI's deaths in Malaysia ranked first among the other placement countries in 2016 - 2019. Then, the cases of human rights violations with PMI's human rights in Malaysia are cases of abuse by employers. The ILO had created the Decent Work Country Programme (DWCP) Indonesia for the 2012 - 2015 period. The DWCP Indonesia was created as the ILO's attention to the vulnerability of PMI in Malaysia. In addition, Malaysia is also a member country of the ILO that is bound by ILO Conventions, ILO Declaration, and ILO's work programmes. Therefore, this research aims to understand cases of human rights violations with PMI in Malaysia in 2016 - 2019, especially cases of violations by employers. Then, this research also aims to describe the roles of ILO to help Indonesia in handling cases of PMI in Malaysia 2016 - 2019.